Nominativnye predloženiâ v naučnoj proze russkogo âzyka (sravnitelʹno s serbskim) - Stoânovič, Andrei (Stylistyka, 1996)
Nominative sentences in Russian and Serbian (genre of text-books and manuals) exhibit a high degree of resemblance as to their function: in both languages they perform the function of a title. Some common characteristics are also shown with regard to the means of expression, the most prominent being wide use within titles of deverbative nouns (Nomina actionis), with acquie thus semi-predicative nature. However, more important interlinguistic resemblance is related to differences in the use of verbs: in the Russian titles examined, verbs are most often omitted, whereas in Serbian they are used more freely. It is probably a consequence of differences between the two grammar systems (limited use of participles in modem Serbian). Although genetic relation between the two Slavic languages is important, future contrastive-stylistic analysis of scientific style should be focused on possible extralinguistic differences (difference in the developmental history of scientific styles and their subsequent growth; differences in language traditions established, in (stylistic) uses accepted; different degree of language editor's interference, etc.).